Game-based learning of science subject for primary school / Siti Rafidah Muhamat Dawam ... [et al.] - Muhamat Dawam, Siti Rafidah; Rosli, Muhammad Alif Haikal; Mat Din, Mazura; Mansor, Shaifizat; Tajuddin, Taniza; Ali, Noor Rasidah (Universiti Teknologi MARA, Negeri Sembilan, 2023)
(NSA) shows that only 19 percent of students in secondary level opted to a science stream since 2020. Among the contributing factors to the lack of interest related to this matter begin at the primary school level which is the uninteresting method of teaching and learning, and the extensive syllabus that leads to difficulty of understanding. Current implementation of teaching and learning in this subject is conducted conventionally and less interactive. Thus, student find the subject is difficult to understand and unexciting. A game-based learning inspired by “Saidina” board game were constructed to attuned for this purpose, namely Saidina Sains Tahun 6 which consists of four challenging Science topics specifically, ‘Mikroorganisma’, ‘Interaksi Antara Hidupan’, ‘Pemeliharaan Dan Pemuliharaan’ and ‘Kestabilan dan Kekuatan’. The game is created to help year 6 students improve their understanding of science subjects on the above topics. A total of 20 respondents was involved in this pilot study whom 90 percent agreed that the procedure or game plan in this method of learning game is clearly described in the rules form with majority agreed that the game is easy to use. 95 percent respondents also support that the game can increase their knowledge in science subject, therefore agreed to use this game in the future and will recommend it to others.